Analisis Motivasi Kerja Generasi Z Yang Dipengaruhi Oleh Lingkungan Kerja dan Komitmen Kerja - Yuli Fajriyanti; Asmadhini Handayani Rahmah; Sofia Ulfa Eka Hadiyanti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research aims to examine the influence of work environment and work commitment on the work motivation of Generation Z employees in Samarinda City. This study employs a quantitative approach with the population being all Generation Z individuals in Samarinda City. The sample consists of 141 respondents obtained through purposive sampling technique. Data collection is conducted using a questionnaire distributed through Google Form using the Likert scale. The analysis technique used is multiple linear regression through the SPSS software. The results of this study indicate that partially, the t-test results show that the work environment (x1) has a significance value of 0.002 ≤ 0.10, which means that the work environment significantly influences the work motivation of Generation Z. The t-test results for work commitment (x2) on work motivation (y) have a significance value of 0.006 ≤ 0.10, indicating that work commitment significantly affects the work motivation of Generation Z. Moreover, simultaneously, the F-test results for both the work environment (x1)and work commitment (x2) on work motivation (y) have a significance value of 0.001 ≤ 0.10, signifying that the work environment and work commitment, when considered together, significantly influence the work motivation of Generation Z.